Estudos sedimentológicos e o contexto estrutural da formação Serra do Martins, nos platôs de Portalegre, Martins e Santana/RN - Menezes, Maria Rosilene Ferreira de (1999)
This dissertation deals with sedimentological and structural framework of the siliciclastic rock of the Serra do Martins Formation (FSM) in the Portalegre, Martins and Santana plateau, located to the south of Potiguar Basin, in the southwest and central Rio Grande do Norte state. This formation, regarded as of Oligo-Miocene age based on intrusive relations of the Miocene Macau volcanics, has a still disputable age due to the lack of appropriate bio and/or chronostratigraphic markers. The FSSM deposits crop out along 650 to 750 m high plateau, as a remanescent sedimentary cover directly overlying topographically uplifted pre-cambrian crystalline rocks. During the last decades, these deposits were interpreted according to a Tertiary paleoclimatic evolutionary model, associated to pedogenetic processes. The sedimentological characterization of the FSM was done through a detailed study of its facies, petrography and diagenetic features. The facies study was based on description of field relations, textures and structures, the piling up of the strata and their lateral variations. The FSM was deposited by an anastomosing to coarse-meandering fluvial system, including deposits of lag, cannel-fill, ouver-bank and flood plain. The petrographic composition of the sediments, coupled to their facies and paleocurrent directions, suggest a rather distal sourcearea, to the south of the present plateau. The diagenetic study identified an incipient grain mechanical compaction, pronounced dissolution of the framework, matrix and/or cement components, intense precipitation of kaolinite, silic and, eventually, iron oxides, besides mechanical infiltration of the clays. Most of these events, regarded in the literature as associated to near-surface conditions (eo or telodiagenesis), indicate the FSM sediments were never deeply buried. Topographic relations along longitudinal and transversal sections reaching the Potiguar Basin to the north identified regional dips that allow to discuss stratigraphic correlations between the FSM and the basin formations. The sedimentological features of the different units and the intrusive relations of the Macau volcanics were also considered in these correlations,which support the Oligo-Miocene age previously accepted for the FSM. Concerning the tectonic framework of the FSM, this work investigated the pre-cambrian to cretaceous heritage and the cenozoic deformation, allowing the recognition of pre-, sin and post-FSM structures. The crystalline basement, belonging to the Seridó Belt, displays NE and WNW foliation trends related to the Brasiliano-age ductile shear zones. In this terrain, brittle-ductile and brittle NE- and NW-trending structures, associated with extensional joints filled with pegmatites and quartz veins, are related to an E-W compression by the end of Brasiliano Cycle. The E-W joints and NE-trending fractures were reactivated by N-S to N-S to NW extension during late Jurassic to Cretaceous times, controlling the emplacement of the Rio Ceará-Mirim basic dyke swarm and the opening of the Potiguar rift basin